The behavior of rubber tyre as fine aggregate in concrete mix - Siti Aza Nurdiana Binti Tajri (School of Environmental Engineering, University Malaysia Perlis, 2014)
Rubber tyres are the most waste material that can be found nowadays. Rubber tyre is the resilient materials that was used by people and make it as the waste tyre disposal after the tyre was not function anymore. Therefore, this material is the one of the largest disposal of waste tyres that had become a major waste management issue in the world at the moment and indirectly can cause air and environment pollution. So that, by replace fine aggregate with rubber tyre it will reduce the pollutions. The purposes of this research are to study the behavior of rubber tyre in concrete mix, to identify physical properties of rubber tyre in concrete mix and to identify engineering properties of modify concrete mix.